Rhodocodon longistamineus (Hyacinthaceae subfam. Urgineoideae), a new species from Madagascar - Martínez-Azorín, Mario; Knirsch, Walter; Andriantiana, Jacky L.; Crespo, Manuel B. (Phytotaxa, 2025)
The study of wild and cultivated material of samples of Rhodocodon collected in the Befandriana-Nord district in Madagascar revealed an undescribed species that shows a unique syndrome of morphological characters, and some deviant characters not reported so far in the genus. Our unpublished phylogenetic study in Rhodocodon confirms its placement in the genus and its independence from other related species. Accordingly, we here describe Rhodocodon longistamineus based on plants presenting a long inflorescence; shortly spurred bracts and small bracteoles; erect-patent, pedicellate, campanulate flowers; elongated tepals very shortly connate at the base, suberect-spreading and overlapping in the basal half, and patent in the upper portion; stamens very shortly adnate to tepals, distinctly elongated and exserted, suberect, slightly incurved and connivent to the ovary at their base, approaching the style along the middle and spreading above; and the distinctly trigonous, narrowly pyramidal, pointed seeds with elongated sinuous testa cells. We provide a complete morphological description as well as data on ecology and distribution.